Integrated Heritage Conservation: Exploring the Role of Community Participation in the Conservation of Thimi - Bhatta, Kishan Datta; Joshi, Buddhi Raj; Paudyal, Sudeep Sharma (Journal of UTEC Engineering Management, 2023)
DOI: https://doi.org/10.36344/utecem.2023.v01i01.006The sustainability of cultural heritage resources is strongly linked to the effective participation of local communities in the conservation and management of these resources (Oladeji, Grace, and Ayodeji, 2022). Integrated heritage conservation is assumed to be an appropriate conservation approach specifically to promote inclusive participation of local communities and sustainable community development in the historic settlements. In this context, considering the case of historic town of Thimi, this study aims to explore the existing context and role of community participation in the planning and conservation of heritage resources and also investigate the context of integrated conservation. Multiple tools of data collection such as Key informant’s interview, household’s surveys, participant observation, informal discussion and archival research have been used. Findings demonstrate that continuous decay and destruction of cultural heritages in Thimi have threatened its unique identity and the traditionally well-sustained community is now degrading and heading towards unsustainability. The context of community participation and conservation also seems weak in promoting sustainable conservation and development in Thimi. It recommends for adopting and implementing inclusive participation of local communities and integrated approach to conservation along with preparing comprehensive policies, plans and legislations for promoting sustainable conservation and community development in the historic settlements.